(3GdJGLs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3bGd CHh YKeGf (B: (3Mci dfG Yf LQjQ Hf GdNWai Cfg ONd Ydi YHO Gdedc hbO haOg GdMLGL Edjg s
(3BNQgG (B:s
(3jfJgi Hbhdg (B: (3bGd ce Nda ef GdHfGJ bdJ SJkG hbGdhG KdGKkG aCWQb edjG Ke QaY QCSg abGd s
(3Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs